The Influence of Supervision and Work Discipline on Employee Performance at PT. Lutvindo Wijaya Perkasa Pekanbaru - Annisa Fiky Rahmaningrum; Suryalena (Formosa Journal of Multidisciplinary Research, 2024)
This study aims to determine and analyze the effect of supervision and work discipline on the performance of employees of PT. Lutvindo Wijaya Perkasa Pekanbaru. The research method used is quantitative. The sample of this study was 57 respondents, using data collection techniques using questionnaires. The data obtained was analyzed through linear regression analysis with the SPSS program. The results showed: (1) There is a significant influence of supervision on the employee performance of PT Lutvindo Wijaya Perkasa Pekanbaru. Obtained t-count value of 8.242> t-table 1.673 with a significant 0.000 <0.05. The results of simple linear regression analysis show that if supervision increases by 0.820, it will increase employee performance by 4.544 constantly. (2) There is a significant influence of work discipline on the performance of employees of PT. Lutvindo Wijaya Perkasa Pekanbaru. Obtained a t-count value of 7.818> t table 1.673 with a significant 0.000 <0.05. The results of simple linear regression analysis show that if work discipline increases by 0.801, it will increase employee performance by 4.010 constantly. (3)